Effective Strategies for Listening Comprehension: A Focus on Asia - Calis, Jonalyn B.; Ngolab, Rebecca D.; Pablo, Sherilyn B.; Saysayap, Angel Faith B.; Pelila, John Rey O. (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Listening, once perceived as the least important language skill, has gained increasing attention recently, as shown by the growing number of studies in the field. However, research on listening comprehension strategies remains limited. This study reviews the most frequently used teaching and learning strategies in Asian classrooms to enhance listening comprehension and identify research gaps for future exploration. A systematic literature review was conducted on studies published between 2021 and 2025 across eight Asian countries: China, Iran, Indonesia, Taiwan, Thailand, Turkey, Saudi Arabia, and South Korea. Findings reveal that the most common teaching strategy is the use of regular and repetitive listening activities, while metacognitive strategies emerge as the most frequently practiced learning approach. Moreover, the review highlights a notable imbalance between the number of strategies examined under learning strategies versus teaching strategies. These results emphasize the need for further research across Asia, particularly studies that design and test innovative strategies aligned with the growing demand for technology-driven and digitally enhanced language instruction.